Global- and Renal-Specific Sympathoinhibition in Aldosterone Hypertension. Issue 6 (June 2015) - Lohmeier, Thomas E.; Liu, Boshen; Hildebrandt, Drew A.; Cates, Adam W.; Georgakopoulos, Dimitrios; Irwin, Eric D.
<x xml:space="preserve">Abstract</x> Recent technology for chronic electric activation of the carotid baroreflex and renal nerve ablation provide global and renal-specific suppression of sympathetic activity, respectively, but the conditions for favorable antihypertensive responses in resistant hypertension are unclear. Because inappropriately high plasma levels of aldosterone are prevalent in these patients, we investigated the effects of baroreflex activation and surgical renal denervation in dogs with hypertension induced by chronic infusion of aldosterone (12 μg/kg per day). Under control conditions, basal values for mean arterial pressure and plasma norepinephrine concentration were 100±3 mm Hg and 134±26 pg/mL, respectively. By day 7 of baroreflex activation, plasma norepinephrine was reduced by ≈40% and arterial pressure by 16±2 mm Hg. All values returned to control levels during the recovery period. Arterial pressure increased to 122±5 mm Hg concomitant with a rise in plasma aldosterone concentration from 4.3±0.4 to 70.0±6.4 ng/dL after 14 days of aldosterone infusion, with no significant effect on plasma norepinephrine. After 7 days of baroreflex activation at control stimulation parameters, the reduction in plasma norepinephrine was similar but the fall in arterial pressure (7±1 mm Hg) was diminished (≈55%) during aldosterone hypertension when compared with control conditions. Despite sustained suppression of sympathetic activity, baroreflex activation did not have central actions to inhibit either the stimulation of vasopressin secretion or drinking induced by increased plasma osmolality during chronic aldosterone infusion. Finally, renal denervation did not attenuate aldosterone hypertension. These findings suggest that aldosterone excess may portend diminished blood pressure lowering to global and especially renal-specific sympathoinhibition during device-based therapy.